ANIPE-Cu Catalyst Enables Highly Enantioselective Markovnikov Hydroboration of α-Olefins - Cai, Yuan; Shi, Shi-Liang (Synlett, 2020)
Asymmetric hydroboration of simple and unactivated terminal alkenes (α-olefins), feedstock chemicals derived from the petrochemical industry, has not been efficiently realized for past decades. Using a bulky ANIPE ligand, we achieved a rare example of highly enantioselective copper-catalyzed Markovnikov hydroboration of α-olefins. The chiral secondary alkylboronic ester products were obtained in moderate to good yields and regioselectivities with excellent enantioselectivities.1 Introduction2 Conditions Optimization3 Substrate Scope4 Application5 Mechanistic Discussion6 Conclusions and Future Directions
Keywords: asymmetric hydroboration; α-olefin; copper catalysis; ligand design; privileged chiral fragment; N-heterocyclic carbine